HUBUNGAN DAYA LEDAK OTOT TUNGKAI TERHADAP KEMAMPUAN JUMP SERVICE PADA TIM BOLA VOLI PUTRA DI SMP N 2 BANGKINANG KOTA - Yosi Arter; Iska Noviardila; Dedi Ahmadi (Jurnal BOLA: Bersama Olahraga Laju Asia, 2024)
Volleyball is a game played by two teams separated by a net, the game uses hands by bouncing. One of the Volleyball playing techniques is the jump serve. Jump service is a service in volleyball that is done with an upper hand service. The aim of this research was to determine the relationship between leg muscle explosive power (vertical jump) and jump service skills in volleyball at SMPN 2 Bangkinang Kota. This type of research is quantitative correlational research. The population in this study was extracurricular volley ball players at SMPN 2 Bangkinang City, totaling 24 people. The sampling technique in this research is the overall sample with a total research sample of 24 people. The sample in this study was 24 male students in grades VII and VIII of SMP N 2 Bangkinang Kota who liked to play volleyball and who had taken part in extracurricular activities in the sport of volleyball. Data collection techniques are observation techniques, library techniques and test or measurement techniques. The test instruments used are the vertical jump test and the service jump test. Based on the calculation results, it can be seen that there is a relationship between the explosive power of the leg muscles and the jump serve with a correlation result of a sig value of 0.000 (< 0.005) and the Pearson table shows a result of 0.167 (16.7%) meaning that there is a positive relationship between the two variables. Based on the categorization results, leg muscle explosive power is in the low category with a percentage value of 38% and jump service ability is in the low category with a percentage value of 42%. It can be concluded that the hypothesis test is strong so it is said to be related